PERAN GURU PENDIDIKAN PANCASILA DALAM MENGUATKAN KARAKTER INTEGRITAS UNTUK MENCIPTAKAN LINGKUNGAN KELAS ANTI PERUNDUNGAN DI SMAN 1 RENGEL - Deeva Putri Salsabilla; Raden Roro Nanik Setyowati (Universitas Negeri Surabaya (Unesa), 2025)
The position held by teachers is as a professional and an agent of learning. This research aims to analyze the role of Pancasila Education teachers and identify obstacles in strengthening integrity character. This study uses a descriptive qualitative research approach. Data collection techniques through observation, interviews, and documentation. Data is analyzed using data collection, data reduction, data presentation, and conclusion drawn. The theoretical basis of this study is the theory of Character Education by Thomas Lickona. The results of the study show that the role of Pancasila Education teachers in strengthening the integrity character to create an anti-bullying classroom environment at SMAN 1 Rengel is, 1) integrating the understanding of integrity values, 2) associating integrity values with Pancasila Education materials, 3) providing motivation to students, 4) not discriminating against students, and 5) forming group work. The obstacles faced by Pancasila Education teachers are, 1) internal factors, namely the sense of superiority in students, 2) external factors consisting of factors that occur during the learning process, namely students do not pay attention to Pancasila Education teachers. From the family environment (related to the relationship established when with the family). And the social environment (related to technological advances (social media) and friendship relationships).